2016
DOI: 10.1186/s12940-016-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood cadmium levels and Alzheimer’s disease mortality risk in older US adults

Abstract: BackgroundCadmium, a ubiquitous environmental pollutant, exhibits potential neurotoxic risk. Although compelling evidence suggests cadmium accumulation has a role in the formation of amyloid-β plaques and neurofibrillary tangles, which are the hallmarks of Alzheimer's disease (AD) pathogenesis, the supporting evidence in humans is limited and conflicting. In this study, we investigated the association between blood cadmium levels and AD mortality among older adults by analyzing the prospective data from the 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 29 publications
3
63
0
Order By: Relevance
“…Jiang et al reported the impact of Cd on the formation of neurofibrillary tangles [52]. Increased blood Cd levels were associated with elevated AD mortality among participants aged 60 years or older in the National Health and Nutrition Examination Survey (NHANES) (1999-2004 cycles) [53]. Similarly, Peng et al showed that urinary Cd was associated with elevated risk of AD mortality among older adults [54].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported the impact of Cd on the formation of neurofibrillary tangles [52]. Increased blood Cd levels were associated with elevated AD mortality among participants aged 60 years or older in the National Health and Nutrition Examination Survey (NHANES) (1999-2004 cycles) [53]. Similarly, Peng et al showed that urinary Cd was associated with elevated risk of AD mortality among older adults [54].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic, low-level Cd exposure in Sweden has been linked to an increased risk of heart failure (Borne et al 2015), while chronic, low-level Cd exposure in the U.S. been linked to death from CVD, heart disease, and coronary heart disease (Tellez-Plaza et al 2012) along with increased death from all causes (Hyder et al 2013;Patel et al 2013), cancer (Adams et al 2012;Lin et al 2014), and Alzheimer's disease (Min and Min 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in risk of heart failure was seen among those with blood levels in the 4 th quartile (HR 1.95, 95% CI 1.02-3.71) after adjustment for age and conventional risk factors and biomarkers. In a follow-up of 4,060 participants in the NHANES 1999(Min and Min 2016, blood Cd levels > 0.6 µg/L were associated with death from Alzheimer's disease (HR 3.83, 95% CI 1.39-10.59). Table 3 provides a summary of studies that quantify oxidative stress and inflammation in relationship to Cd exposure.…”
Section: Cadmium Exposure and Mortalitymentioning
confidence: 99%
“…During the last recent decades, the concern about the adverse effects of cadmium (Cd 2+ ) ions on memory function and neural apoptosis has been increased worldwide . Cadmium is one of the most widely distributed heavy metals on the earth crust that is abundantly found in drinking water, food, industrial compounds, and smoking and has a long biological life within contminated tissues (up to 30 years) .…”
Section: Introductionmentioning
confidence: 99%